2010
DOI: 10.1016/j.electacta.2010.08.067
|View full text |Cite
|
Sign up to set email alerts
|

Tribocorrosion behaviour of TiC O thin films in bio-fluids

Abstract: This version is available at https://strathprints.strath.ac.uk/18850/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 37 publications
(53 reference statements)
2
28
0
Order By: Relevance
“…Over past few years, investigations on tribocorrosion of materials subjected to corrosion and wear are a research hot spot. Efforts have been made to identify the synergistic effect between corrosion and wear and quantify the synergistic components by mathematical model . Most studies have found that synergistic effect between corrosion and wear leads to total material loss far more than the sum of wear and corrosion alone .…”
Section: Introductionmentioning
confidence: 99%
“…Over past few years, investigations on tribocorrosion of materials subjected to corrosion and wear are a research hot spot. Efforts have been made to identify the synergistic effect between corrosion and wear and quantify the synergistic components by mathematical model . Most studies have found that synergistic effect between corrosion and wear leads to total material loss far more than the sum of wear and corrosion alone .…”
Section: Introductionmentioning
confidence: 99%
“…Although one previous study suggested that both Ti alloy and CpTi have similar basic corrosive behavior, a future study is needed to test the response of CpTi when exposed to similar conditions. In addition, further studies are required to examine the degradation properties of the implant surface under simultaneous mechanical and electrochemical influence (known as tribocorrosion) …”
Section: Resultsmentioning
confidence: 99%
“…In addition, further studies are required to examine the degradation properties of the implant surface under simultaneous mechanical and electrochemical influence (known as tribocorrosion). 49,50 This study can also be extended to understand the cellular response of osteoblast cells to corroded surfaces resulting from nicotine consumption. Reporting specific chemical reactions and subsequent corrosion kinetics are beyond the scope of the current article due to limitations in the testing methods; however, they will be considered in future work.…”
Section: Clinical Relevance and Future Scopementioning
confidence: 99%
“…Indeed, many efforts have been made to improve the tribocorrosion performance of biodemical alloys by surface coatings, including diamond‐like carbon coatings, ion implantation, TiN and TiC based coatings, CrN based coatings and surface alloying . In particular, detailed studies have been performed on the potential of S‐phase coating and CrN coating to improve the tribocorrosion behavior of biomedical alloys .…”
Section: Introductionmentioning
confidence: 99%